THE ROLE OF INFORMATION TECHNOLOGIES IN TOURISM DEVELOPMENT (Development Service Industry Management, 2025)
The article presents a classification of the main information technologies applied in tourism, including official websites, mobile applications, online booking platforms, CRM systems, social media integration, big data analytics, chatbots, artificial intelligence, and elements of virtual and augmented reality. The functions of IT in the tourism sector are defined, encompassing sales organization, communication, customer relationship management, analytics, marketing, logistics, and strategic planning. The current state of IT implementation in Ukraine’s tourism industry is analyzed. Despite a positive trend toward digitalization, several constraining factors are identified, such as insufficient IT competencies among employees, limited funding for innovations, and the lack of an integrated national strategy for digital development in the sector. A SWOT analysis clearly outlines strengths (existing IT infrastructure, customer openness to digital solutions), weaknesses (low personnel qualifications, lack of investment), opportunities (development of digital services, cooperation with tech companies), and threats (cybersecurity, high competition, technological backwardness of some enterprises). Based on the research findings, a number of practical recommendations are proposed for tourism companies to enhance their competitiveness through modern IT solutions. These include the implementation of CRM systems, AI-powered chatbots, decision-making analytics tools, online booking platforms, and the use of augmented and virtual reality technologies. The study also emphasizes the need for investment in digital staff education and the gradual, phased introduction of innovations with continuous evaluation of their effectiveness.
Keywords: tourism; information technologies; digitalization; tourism enterprises; Ukraine